Depletion of Complement Enhances the Clearance of Brucella abortus in Mice - González-Espinoza, Gabriela (Infect Immun, 2018)
Brucellosis is a bacterial disease of animals and humans. Brucella abortus barely activates the innate immune system at the onset of infection, and this bacterium is resistant to the microbicidal action of complement. Since complement stands as the first line of defense during bacterial invasions, we explored the role of complement in B. abortus infections. Brucella abortus-infected mice depleted of complement with cobra venom factor (CVF) showed the same survival rate as mice in the control group. The complement-depleted mice readily eliminated B. abortus from the spleen and did so more efficiently than the infected controls after 7 days of infection. The levels of the proinflammatory cytokines tumor necrosis factor alpha and interleukin-6 (IL-6) remained within background levels in complement-depleted B. abortus-infected mice. In contrast, the levels of the immune activator cytokine gamma interferon and the regulatory cytokine IL-10 were significantly increased. No significant histopathological changes in the liver and spleen were observed between the complement-depleted B. abortus-infected mice and the corresponding controls. The action exerted by Brucella on the immune system in the absence of complement may correspond to a broader phenomenon that involves several components of innate immunity.